STRATEGIC SCHOOL LEADERSHIP IN STUDENT ADMISSION MANAGEMENT: A QUALITATIVE CASE STUDY AT A PUBLIC JUNIOR HIGH SCHOOL IN INDONESIA - Dwi Nurdiantika (Jurnal Manajemen Pendidikan, 2026)
Effective student admission management has become an increasingly important issue for public schools facing growing competition in attracting prospective students while maintaining educational quality. This study aims to explore the strategic leadership practices employed by the principal of SMP Negeri 19 Jambi in improving student enrollment through comprehensive planning, stakeholder collaboration, and institutional management. A qualitative case study approach was employed to obtain an in-depth understanding of leadership practices within the school's natural setting. Data were collected through semi-structured interviews, participant observation, and document analysis involving the principal, vice principal, teachers, administrative staff, and school committee representatives. The data were analyzed using the interactive model of data analysis, including data condensation, data display, and conclusion drawing, while credibility was strengthened through source, technique, and time triangulation. The findings reveal that student admission management was implemented through four interrelated strategic dimensions: strategic planning, institutional promotion and community engagement, collaborative stakeholder involvement, and continuous evaluation of admission outcomes. The principal also strengthened school competitiveness by optimizing digital communication, improving educational services, and fostering partnerships with surrounding communities. These integrated leadership practices contributed to increased public trust and improved student enrollment.